2018
DOI: 10.1038/s41385-018-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

T cell-directed IL-17 production by lung granular γδ T cells is coordinated by a novel IL-2 and IL-1β circuit

Abstract: Immune-mediated lung is considered the result of an exacerbated innate injury immune response, although a role for adaptive lymphocytes is emerging. αβ T cells specific for S. aureus enterotoxin A orchestrate a Tγδ17 response during lung injury. However, the mechanism driving IL-17 production is unclear. Here, we show a role for IL-2 triggering IL-17 production by lung granular γδ T cells as IL-17 synthesis and neutrophil recruitment was reduced by IL-2 blocking mAbs in vitro and in vivo. Mass cytometry analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
11
1
1
Order By: Relevance
“…JES6-IL-2C administration also induces a marked expansion of gd T cells in the spleen and a significant but smaller response in the lung. In contrast to the beneficial outcomes reported in this study, IL-2 stimulation of gd T cells and the subsequent production of IL-1 has recently been reported to compromise lung integrity (32). The opposing actions of IL-2 signals and the outcome of inflammatory cytokine production are perplexing, and further experiments are thus needed to address the precise roles of ILC, Tregs, and gd T cells in the responses summarized in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…JES6-IL-2C administration also induces a marked expansion of gd T cells in the spleen and a significant but smaller response in the lung. In contrast to the beneficial outcomes reported in this study, IL-2 stimulation of gd T cells and the subsequent production of IL-1 has recently been reported to compromise lung integrity (32). The opposing actions of IL-2 signals and the outcome of inflammatory cytokine production are perplexing, and further experiments are thus needed to address the precise roles of ILC, Tregs, and gd T cells in the responses summarized in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…To dissect the precise role of NAM during in vivo T cell responses we took advantage of S. aureus enterotoxin A, an immunogen that directly activates specific TCR Vβ chains (e.g., Vβ3) but not Vβ14 ( Herman et al., 1991 ). When delivered intranasally, this model induces acute lung injury ( Kumar et al., 2010 ; Menoret et al., 2018 ; Svedova et al., 2017 ), leading to life threatening complications including diffuse alveolar damage (DAD), acute lung injury (ALI), and acute respiratory distress syndrome (ARDS). Secondly, this response greatly impacts CD8 + T cells and IFNγ ( Muralimohan et al., 2008 ) which we have shown are targets for NAM.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Tcrd-deficient animals were less efficient at bacterial clearance, they had overall more severe immunopathology during the first 48 h after infection [50]. Vella and colleagues used a mouse model of intranasal administration of S. aureus enterotoxin A (SEA) and showed that γδ T cells rapidly respond by producing IL-17 in a mechanism that depended on the presence of functional αβ T cells and the production of both IL-2 and IL-1β [51,52]. Using an intratracheal infection model, it was shown that S. aureus can cause NLRC4-driven necroptosis and production of IL-18, both of which suppress γδT17 cells and prevent infection clearance [53].…”
Section: Bacterial Infectionsmentioning
confidence: 99%